2015
DOI: 10.1515/abcsb-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Cytological Analysis of Microsporogenesis and Microgametogenesis of the Invasive Species Galinsoga quadriradiata Ruiz & Pav. (Asteraceae)

Abstract: Acta Technologica Agriculturae 1/2016Dušan Páleš et al.The most effective way for determination of curves for practical use is to use a set of control points. These control points can be accompanied by other restriction for the curve, for example boundary conditions or conditions for curve continuity (Sederberg, 2012). When a smooth curve runs only through some control points, we refer to curve approximation. The B-spline curve is one of such approximation curves and is addressed in this contribution. A specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Mature pollen grains of C. kilaea contain insoluble polysaccharides and proteins. Similar observations have been also reported in Galinsoga quadriradiata (Kolczyk et al 2015). Although C. kilaea is a tetraploid species (2n = 4x = 36) (Meric et al 2010), meiosis is quite regular and the pollen fertility percentage is high (87%).…”
Section: Discussionsupporting
confidence: 75%
“…Mature pollen grains of C. kilaea contain insoluble polysaccharides and proteins. Similar observations have been also reported in Galinsoga quadriradiata (Kolczyk et al 2015). Although C. kilaea is a tetraploid species (2n = 4x = 36) (Meric et al 2010), meiosis is quite regular and the pollen fertility percentage is high (87%).…”
Section: Discussionsupporting
confidence: 75%
“…The morphology of the pollen wall is essential, among other things, to correlate the type of ornamentation with reproductive strategies, as in some invasive plants (Syamsuardi et al 2018). For instance, Kolczyk et al (2015) demonstrated that some cytological features, such as the regular and proper course of meiosis and high viability of pollen grains, lead to the formation of aggressive weedy races that can colonize highly disturbed ecological habitats. In Quaternary botany, palynological records provide a reliable approach to determining the native or introduced status of a species in a particular region (Birks 2019).…”
Section: Discussionmentioning
confidence: 99%